2017
DOI: 10.1136/bjophthalmol-2017-311000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of autofluorescence and OCT angiography in Stargardt disease

Abstract: RPE damage on FAF appears to be significantly larger than CC layer vessel loss on OCTA, which suggests that RPE damage might precede that of CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…Guduru et al compared RPE atrophy on fundus autofluorescence imaging and hypointensity at the choriocapillaris layer on OCTA in 22 STGD patients (43 eyes), and found that the RPE atrophy area (6.7 ± 4.4 mm 2 ) was larger than the choriocapillaris hypointense area (4.2 ± 3.6 mm 2 ) (p = 0.004). Those data suggested that RPE damage may precede choriocapillaris atrophy in STGD [43]. Functionally, Mastropasqua and colleagues examined 17 eyes from 9 patients with STGD and found that the percent perfused choriocapillaris area was associated with retinal sensitivity analyzed by microperimetry (p < 0.001), thereby suggesting the possibility of utilizing choriocapillaris dysfunction as a predictor for retinal function in STGD patients [44].…”
Section: Octa In Stargardt Diseasementioning
confidence: 99%
“…Guduru et al compared RPE atrophy on fundus autofluorescence imaging and hypointensity at the choriocapillaris layer on OCTA in 22 STGD patients (43 eyes), and found that the RPE atrophy area (6.7 ± 4.4 mm 2 ) was larger than the choriocapillaris hypointense area (4.2 ± 3.6 mm 2 ) (p = 0.004). Those data suggested that RPE damage may precede choriocapillaris atrophy in STGD [43]. Functionally, Mastropasqua and colleagues examined 17 eyes from 9 patients with STGD and found that the percent perfused choriocapillaris area was associated with retinal sensitivity analyzed by microperimetry (p < 0.001), thereby suggesting the possibility of utilizing choriocapillaris dysfunction as a predictor for retinal function in STGD patients [44].…”
Section: Octa In Stargardt Diseasementioning
confidence: 99%
“…Die OCTA ist geeignet, die Progression makulärer vaskulärer Veränderungen bei Retinitis pigmentosa im Verlauf zu messen [38]. Beim Morbus Stargardt ist die FAF sensitiver als die OCTA [39].…”
Section: Nahinfrarot-autofluoreszenz (Nia)unclassified
“…These findings purported a cause-effect relationship between the morphological changes seen in retinal microstructure and the status of vascular nourishment, in the sense that one pathology is a consequence of the other, though the exact mechanism remains debatable [13][14][15]. One theory proposes that the progressive demise of photoreceptors and RPE causes a thinning out of the retina with subsequent progressive atrophy of retinal vasculature and choriocapillaris as part of a downregulation process due to a reduced vascular demand [16]. Another proposed mechanism is that retinal thinning due to the loss of photoreceptors and RPE allows more oxygen influx into the inner retinal layers from the choroidal circulation.…”
Section: Theories Of Pathogenesis Of Vascular Changes In Macular Dystmentioning
confidence: 99%
“…Another plausible theory is that progressive RPE loss results in a decreased release of vascular endothelial growth factor (VEGF) and other signaling factors that are essential for the viability of the choriocapillaris, hence precipitating choriocapillaris atrophy [17][18][19]. Finally, some researches propose that mechanical compression by the lipofuscin-laden RPE and accumulation of hyaline deposits between the RPE and Bruch's membrane exerts mechanical compression on the choriocapillaris with subsequent atrophy and loss [16].…”
Section: Theories Of Pathogenesis Of Vascular Changes In Macular Dystmentioning
confidence: 99%
See 1 more Smart Citation